2013
DOI: 10.1080/13662716.2013.791125
|View full text |Cite
|
Sign up to set email alerts
|

Follow the (Industry) Money – The Impact of Science Networks and Industry-to-University Contracts on Academic Patenting in Nanotechnology and Biotechnology

Abstract: We investigate the factors influencing an academic's propensity to patent and the quality of patenting in nanotechnology and biotechnology. We find that a university researcher is more likely to be listed as an inventor of a patented innovation, regardless of the assignee, if he receives private funding, has a fairly high level of cliquishness in the scientific network and has shown a prior capacity to successfully collaborate with industry, a concept that we name innovation loops. Furthermore, citation rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…These results suggest some level of review validity, although it is still unclear how and to what extent the funding can promote patent creation. It may be the direct effect is small; while some have observed small positive impacts on patent generation (Payne and Siow, 2003) or on patent originality and impact (Huang et al, 2006;Guerzoni et al, 2014), some have found no effect or even a negative effect (Sanyal, 2003;Beaudry and Kananian, 2013). Thus, patent productivity has some promise for use in tests of review validity, however future studies will likely require more subtle, nuanced approaches.…”
mentioning
confidence: 99%
“…These results suggest some level of review validity, although it is still unclear how and to what extent the funding can promote patent creation. It may be the direct effect is small; while some have observed small positive impacts on patent generation (Payne and Siow, 2003) or on patent originality and impact (Huang et al, 2006;Guerzoni et al, 2014), some have found no effect or even a negative effect (Sanyal, 2003;Beaudry and Kananian, 2013). Thus, patent productivity has some promise for use in tests of review validity, however future studies will likely require more subtle, nuanced approaches.…”
mentioning
confidence: 99%
“…Interestingly, the more scientists work with industry, the more they bypass their technology transfer office when patenting (Goel and Göktepe-Hultén, 2018), meaning these patents are assigned to an external entity and not their university -a phenomenon highlighted by a recent study of a UK research university . Finally, having been contracted by a firm in the past positively influences patenting volume and quality for Quebecois academics (Beaudry and Kananian, 2013) and spending time collaborating with industry positively influences the propensity of US academics to patent and commercialise within those collaborations (Libaers, 2017), although yet again in both cases the relationship shows an inverse U-shape. However, Bikard et al (2019) provide a dissenting result using international data, suggesting that academics who work with industry patent less than comparable colleagues not working with industry; they suggest that this may be due to the fact that mixed academia-industry teams establish a division of labour where academics focus on publishing while industry partners focus on patenting.…”
Section: Commercial Consequencesmentioning
confidence: 97%
“…Often collaborations connect individual scholars far beyond their own teams and organizations. Consequently, innovation and technological change in nanotechnology emerge from efforts of scholarly networks rather than from individual efforts (Beaudry and Kananian 2013;Powell et al 1996). Its potential can be only realized in world-wide international and inter-organizational collaboration networks (Pandza et al 2011).…”
Section: Characteristics and Potential Of Nanotechnologymentioning
confidence: 99%